Childhood Vaccinations and Demographic Transition: Long-Term Evidence from India - Arindam Nandi; Amit Summan; D. Thoai Ngô; David E. Bloom (Institute of Labor Economics (IZA), 2022)
Childhood vaccines can increase population growth in the short term by improving the survival rates of young children. Over the long run, reductions in child mortality rates are associated with lower demand for children and fertility rates (known as "demographic transition"). Vaccines can potentially aid demographic transition by lowering child mortality and improving future health, schooling, and labor market outcomes of vaccinated mothers, but these long-term demographic benefits remain untested. In this study, we examine the demographic effects of India's national childhood vaccination program (the Universal Immunization Programme or UIP). We combine data on the district-wise rollout of UIP during 1985–1990 with fertility preference data of 625,000 adult women from the National Family Health Survey of India 2015–2016. We include women who were born five years before and after the rollout period (1980–1995) and were cohabiting with a partner at the time of the survey. We divide these 20-36-year-old women into two groups: those who were exposed to UIP at birth (treatment group) and those who were born before the program (control group). After controlling for individual- and household-level factors and age and district fixed effects, treatment group women are 2% less likely to have at least one child and want 2% fewer children in their lifetime as compared with the control group. The negative effect on at least one childbirth is larger for more educated and richer women, while the effect on the desired number of children is larger for uneducated and poorer women.
Keywords: I15; J13; J18; I10; 330; India; UIP; demographic transition; demand for fertility